On Revelations and Revolutions: Drinking Ayahuasca Among Palestinians Under Israeli Occupation - Roseman, Leor; Karkabi, Nadeem (Frontiers in Psychology, 2021)
The ritualistic use of ayahuasca can induce a feeling of unity and harmony among group members. However, such depoliticized feelings can come in the service of a destructive political status quo in which Palestinians are marginalized. Through 31 in-depth interviews of Israelis and Palestinians who drink ayahuasca together, and through participatory observations, such rituals were examined. In this setting marginalization was structurally rooted by the group’s inability to recognize Palestinian national identity or admit the ongoing Israeli injustice toward Palestinians. Although the groups avoided politics, they still find their way into these rituals. This happened through occasional ayahuasca-induced revelatory events, in which individuals were confronted with a pressing truth related to the oppressive relations between Jewish Israelis and Palestinians. Three case studies of such revelatory events are described in this paper. Affected by emotions of pain, anger, and guilt, these participants developed resistance toward the hegemonic Israeli ritual structure. This was followed by an urge to deliver an emancipatory message to the rest of the group, usually through a song. Moreover, affected subjects developed a long-lasting fidelity to the truth attained at these events. In time, this fidelity led to the expansion of ayahuasca practices to other Palestinians and the politicization of the practice. The article draws on Badiou’s theory in Being and Event (1988) to analyze the relations between the Israeli ritual structure, the Palestinian revelatory event, and the emancipatory fidelity that followed. Badiou’s theory elucidates the egalitarian revolutionary potential, which is part of the sociopsychopharmacology of psychedelics.